USE OF VERMICOMPOST IN ENHANCING THE GROWTH OF PAKCHOY PLANTS (Brassica rapa L.) - Maria Apriyanti Man; Erminia Pereira Dos Santos; Yosni Kiuk; Onesimus Ke Lele; Frengky Lampu Apu; Siti Rahmah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Pakcoy (Brassica rapa L.) is a popular vegetable among Indonesian communities due to its rich content of vitamins and nutrients. During its growth stage, pakcoy requires essential nutrients to stimulate its growth, hence the use of organic fertilizer such as vermicompost as a nutrient source. This research aimed to investigate the effect of vermicompost dosage on the growth and yield of pakcoy. The study at PT. Bali Organik Internasional. There were four treatments applied: K0 (0 g/plant), K1 (150 g/plant), K2 (200 g/plant), and K3 (250 g/plant). The experimental design used was a completely randomized design (CRD) with four replications, resulting in 16 experimental units. Data were analyzed using analysis of variance (ANOVA) followed by Duncan's at a significance level of 5%. The results indicated that the application of vermicompost dosage significantly influenced the growth and yield of pakcoy. Application of vermicompost at K3 dosage (250 g/plant) resulted in the best performance across all parameters (plant height, leaf number, fresh weight of shoots, fresh weight of roots, and root length) for pakcoy.